Impact of the COVID-19 pandemic on physical activity among university students in Pavia, Northern Italy. - Bertocchi , Lucia; Vecchio, Riccardo; Sorbello, Sebastiano; Correale, Luca; Gentile, Leandro; Buzzachera, Cosme; Gaeta, Maddalena; Odone, Anna (Acta Biomedica Atenei Parmensis, 2021)
Aim: To evaluate the University of Pavia students about physical activity (PA) changes before, during and after the COVID-19 pandemic.Methods: The International Physical Activity Questionnaires (IPAQ) survey was employed to evaluate the PA in three periods: the pre-pandemic period, during national stay-at-home order (March 9th - May 4th 2020), current PA. Exercise intensity for each period was defined using the Metabolic Equivalent of Task (Met) as unit of measurement. The questionnaire was administered online to university students from June 9th to July 4th 2021, structured in four sections, also collecting demographic data.Results: 55,6% of the study population reported a significant decrease in PA during lockdown. The number of active/very active subjects dropped from 72.2% in pre-pandemic period to 29.6% during containment measures. 50% reported a substantial increase in moving out of the lockdown. Stay-at-home order was associated with an increase in sedentary lifestyle (68.5%), which sharply decreased moving out from lockdown (two-third of study population). Average time in minutes spent sitting was 612 before pandemic, 844 during the pandemic and 670 after social restrictions.Conclusions: Lockdown had a negative impact on PA among the university students leading to an increase in sedentary behaviours. Following the gradual relaxation of the restrictive measures, situation has improved, without however returning to pre-pandemic level. It is of fundamental importance to study new strategies to promote healthy lifestyles while coping with the on-going pandemic.